Mycobacterium - Research and Development 2018
DOI: 10.5772/intechopen.72027
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Factors and Pathogenicity of Mycobacterium

Abstract: Virulence, is referred as the ability of a pathogen to cause disease, and for mycobacteria it depends on their ability to reside within host cells and evade the microbicidal mechanisms of macrophages. The outcome of tuberculosis (TB) infection is highly variable and it seems that the closest relationship between the Mycobacterium genre and humans has shaped the mycobacterial genome to encode bacterial factors that reflects a highly evolved and coordinated program of immune evasion strategies that interfere wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 120 publications
0
17
0
1
Order By: Relevance
“…In Mycobacterium , EVs are mainly composed of cytotoxins and other virulent factors. They infect the host cells by releasing their EV content [ 59 ]. In a study, Marsollier et al [ 60 ] demonstrated that Mycobacterium ulcerans EVs containing cytotoxin mycolactone showed potent pathogenicity in the host when compared to its isolated form.…”
Section: Role Of Evs In Virulencementioning
confidence: 99%
“…In Mycobacterium , EVs are mainly composed of cytotoxins and other virulent factors. They infect the host cells by releasing their EV content [ 59 ]. In a study, Marsollier et al [ 60 ] demonstrated that Mycobacterium ulcerans EVs containing cytotoxin mycolactone showed potent pathogenicity in the host when compared to its isolated form.…”
Section: Role Of Evs In Virulencementioning
confidence: 99%
“…Mycobacterial virulence is associated with the ability of these bacteria to reside within host cells and evade the microbicidal mechanisms of macrophages (Echeverria‐Valencia et al. ). Granuloma formation by M. marinum is linked to virulence (Volkman et al.…”
Section: Discussionmentioning
confidence: 99%
“…The complex pathogenicity of MtbC is determined by a plethora of virulence factors and literature dedicated to these factors is vast. 5,41,42 This is particularly important in the disease process and gives TB a peculiar progression of biological events and interaction with the immune cells.…”
Section: Virulence and Pathogenesis Factors Of Mycobacterium Tuberculmentioning
confidence: 99%